2022
DOI: 10.1080/23320885.2022.2039667
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment using cross-leg free flap and the Masquelet technique: a report of two cases

Abstract: We introduce a treatment that combines the cross-leg free flap with the Masquelet technique and describe two cases using this method for bone and soft tissue reconstruction. Both patients were successfully treated and ambulatory. This novel method can be safely performed using the delay technique, indocyanine-green angiography and near-infrared spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Our systematic review of the literature shows that CLFFs have been used to treat a broad range of severe tissue defects when using recipient vessels was not feasible (Zhang et al, 2012a; Bali et al, 2020; Bishop et al, 2018; Cipriani et al, 1999; Ciudad et al, 2020; Gencel et al, 2016; Zhang et al, 2012b; Hamdi et al, 2000; Hodgkinson et al, 1994; Jin et al, 2022; Karşıdağ et al, 2011; Kesiktas et al, 2006; Lai et al, 1991; Lu et al, 2013; Manrique et al, 2018; Ninkovic et al, 2000; Osaki et al, 2022; Sengezer et al, 1997; Serel et al, 2006; Topalan & Ermis, 2001; Townsend, 1987; Turgut et al, 2010; Woo et al, 2006; Yu et al, 1983; Yu et al, 2012). In addition to soft tissue reconstruction, and in keeping with the first description of CLFF, authors such as Yu et al and Ciudad et al reported the inclusion of osseous components.…”
Section: Discussionmentioning
confidence: 99%
“…Our systematic review of the literature shows that CLFFs have been used to treat a broad range of severe tissue defects when using recipient vessels was not feasible (Zhang et al, 2012a; Bali et al, 2020; Bishop et al, 2018; Cipriani et al, 1999; Ciudad et al, 2020; Gencel et al, 2016; Zhang et al, 2012b; Hamdi et al, 2000; Hodgkinson et al, 1994; Jin et al, 2022; Karşıdağ et al, 2011; Kesiktas et al, 2006; Lai et al, 1991; Lu et al, 2013; Manrique et al, 2018; Ninkovic et al, 2000; Osaki et al, 2022; Sengezer et al, 1997; Serel et al, 2006; Topalan & Ermis, 2001; Townsend, 1987; Turgut et al, 2010; Woo et al, 2006; Yu et al, 1983; Yu et al, 2012). In addition to soft tissue reconstruction, and in keeping with the first description of CLFF, authors such as Yu et al and Ciudad et al reported the inclusion of osseous components.…”
Section: Discussionmentioning
confidence: 99%